2020
DOI: 10.51985/jbumdc2020039
|View full text |Cite
|
Sign up to set email alerts
|

Self-Medication Among Undergraduate Students

Abstract: Objective: To evaluate the frequency of self-medication among undergraduate students of medical sciences Study design and setting: Cross-sectional Study was conducted at Al-Tibri Medical College Hospital, from October 2019 to February 2020. Methodology: Data was collected after an ethical approval of concerned institute; total of 150 students included from the 1st, 3rd and final year of MBBS. Valid questionnaire was used to evaluate the response of the participants regarding selfmedication. Verbal consent was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Update medical curriculum to give information about unethical aspect of self-medication (Khan et al, 2020) Change the method of learning and change the concept of self-medication (Karmacharya et al, 2018)…”
Section: Discussionmentioning
confidence: 99%
“…Update medical curriculum to give information about unethical aspect of self-medication (Khan et al, 2020) Change the method of learning and change the concept of self-medication (Karmacharya et al, 2018)…”
Section: Discussionmentioning
confidence: 99%
“…Practicing self-medication is indeed becoming very common among health professional students, who have a higher exposure to the knowledge of different drugs during their training period than the general population. Studies have shown that self-medication has a higher prevalence among medical students [20][21][22][23]. They have easy access to information from Asian J Pharm Clin Res, Vol 17, Issue 5, 2024, 22-28…”
Section: Introductionmentioning
confidence: 99%